Soviet economic facts, 1917-1970 - Clarke, Roger A. (London: Macmillan Press Limited, 1972)
The book is compiled from original U.S.S.R sources exclusively, so that it can be used as a source equivalent to the official publications.
Bibliography: p. 145-147.
aia 15/10/2018
Loans
Keywords: Economic growth; Economic development; Economic conditions; Soviet Union